2016
DOI: 10.1002/spp2.1047
|View full text |Cite
|
Sign up to set email alerts
|

Gastropods from the Carboniferous (Namurian) of Congleton Edge, Cheshire,UK

Abstract: Gastropod assemblages of late Carboniferous age (Namurian; Chokierian–Alportian) from the Morridge Formation at Pot Bank Quarry, Congleton Edge, Cheshire, contain 27 species, the most diverse gastropod fauna known from the Silesian of the southern UK. Chokierian sandstones yield a sparse assemblage of mainly high‐spired Stegocoelia and bivalves, but flooding associated with the Hudsonoceras proteus marine band (basal Alportian) introduced a diverse invertebrate fauna in which the gastropod fraction is dominate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 65 publications
(191 reference statements)
1
10
0
Order By: Relevance
“…Similar spiral cords are also present in some species of Glabrocingulum such as the specimens placed in Glabrocingulum ( Ananias ) cf. talpaensis in this study and Glabrocingulum ( Glabrocingulum ) armstrongi reported by Peel (2016, fig. 9Q).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Similar spiral cords are also present in some species of Glabrocingulum such as the specimens placed in Glabrocingulum ( Ananias ) cf. talpaensis in this study and Glabrocingulum ( Glabrocingulum ) armstrongi reported by Peel (2016, fig. 9Q).…”
Section: Discussionsupporting
confidence: 79%
“…talpaensis differs from other Glabrocingulum species studied here in having spiral cords on its early teleoconch and in being very small. Peel (2016, fig. 9Q) figured the juvenile whorls of G. ( G .)…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations